The Influence of WOM and Brand Image on Customer Trust and Satisfaction at BANK CENTRAL ASIA (BCA) - Lilik Indrawati; Thyophoida Wanty Suriany Panjaitan (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: The purpose of this study was to determine the satisfaction of BCA customers in Surabaya, through Word of Mouth (WOM), Brand Image, and Trust.